An Investigation of Current Research Support Services in Hungarian Academic Libraries - Dessa, Habtamu; Dani, Erzsébet (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
Traditionally, librarians were more concerned with issues such as the acquisition and organization of library collections, as well as searching and retrieving information for researchers. However, since the introduction of the Internet in the 1990s and advance in ICT, academic library became more concerned with scholarly communication, than searching and retrieval services. This study explores the current practices of research support related to open access, bibliometric and research data management services offered in Hungarian academic libraries. The study applied both qualitative and quantitative research method. Primarily, we analysed websites of ten selected Hungarian academic libraries and detail content analysis of the websites was conducted from 1 July to 30 October 2023. Our investigation shows that, Hungarian university libraries are currently offering broad range of research support services to academic community beyond the traditional research support. Mainly, Hungarian academic libraries have strong culture of open access support to facilitate knowledge transfer. However, from library home page of respective universities, we observe that the practice of bibliometric and research data management services is at its infancy. From website analysis, currently very few of Hungarian university libraries were offering bibliometric and research data management services to academic community.